Distribution, sources and toxicity potential of hydrocarbons in harbor sediments: A regional assessment in SE Brazil. Issue 1 (15th July 2017) - Pinheiro, Pedro P.O.; Massone, Carlos G.; Carreira, Renato S.
Abstract: Aliphatic and polycyclic aromatic hydrocarbons (PAHs) were quantified in harbors sediments from SE Brazil. The aims were to (i) compare harbors with distinct sizes and under the influence of different environmental pressures with respect to the sources and level of hydrocarbon contamination and (ii) evaluate the potential of adverse biological effects of sediment contamination by PAHs, based on sediment quality guidelines and toxicity equivalence quotient. The concentrations of total aliphatics (39.9 μg g − 1 ; 22.9–113 μg g − 1 ) and total PAHs (727 ng g − 1 ; 366–1760 ng g − 1 ) varied according to the size of and urban development around each harbor. Mixed contamination by petrogenic and pyrolytic hydrocarbons, and input of biogenic compounds, indicated the influence of both harbor activities and a myriad of urban, industrial and atmospheric inputs. The quality of sediment poses a risk to benthic biological communities, and, if dredged, this material may cause environmental damage in the waste disposal area. Graphical abstract: Highlights: Sediment quality from different harbors in SE Brazil was compared for the first time. Contamination levels were associated to harbor activities and external sources. Dredging activities in the harbors must account for potential environmental impacts. Management would benefit from the revision of current sediment quality guidelines.